2022
DOI: 10.18632/aging.203729
|View full text |Cite
|
Sign up to set email alerts
|

The effects of metformin and alendronate in attenuating bone loss and improving glucose metabolism in diabetes mellitus mice

Abstract: Background: To explore the anti-osteoporosis and anti-diabetes effects and potential underlying mechanisms of treatment with metformin and alendronate in diabetes mellitus mice. Methods: Eight-week-old C57 BL/KS db/db and db/+ female mice were evaluated according to the following treatment group for 12 weeks: control group, diabetes mellitus group, diabetes mellitus with metformin group, diabetes mellitus with Alendronate group, diabetes mellitus with metformin plus alendronate group. Glucose level,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Balaji et al [40] found that alendronate can reduce the risk of type 2 diabetes in the Indian population. Previous population-based cohort studies have also found that bisphosphonate exposure is related to a decreased risk of type 2 diabetes [39,41], but the clear mechanism of action between the two remains unclear.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Balaji et al [40] found that alendronate can reduce the risk of type 2 diabetes in the Indian population. Previous population-based cohort studies have also found that bisphosphonate exposure is related to a decreased risk of type 2 diabetes [39,41], but the clear mechanism of action between the two remains unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Compared with the first two generations of drugs, it has stronger anti-bone resorption and no bone mineralization inhibition [38]. Zhou et al [39] observed that in C57BL mice, the use of alendronate alone can significantly increase serum glucagon-like peptide-1 levels compared with the diabetes group. Balaji et al [40] found that alendronate can reduce the risk of type 2 diabetes in the Indian population.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of expression of bone metabolisms, glucose metabolism, and inflammation‐related genes, such as Endothelial PAS Domain Protein 1 (EPAS1), Transmenbrane glycoprotein mucin1 (MUC1), CD44 Molecule (CD44), SLC2A1, Cyclin‐Dependent Kinase Inhibitor 1A (CDKN1A), and Dual Specificity Phosphatase 1 (DUSP1), have been uploaded in Table S1 . With the Sham group as the baseline, the mRNA of on‐related genes such as EPAS1, MUC1, CD44, SLC2A1, CDKN1A, and DUSP1 is computed (Zhou et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Intraperitoneal Injection of Glucose Tolerance Test (IPGTT): IPGTT was performed in all animals at 8 and 10 weeks of the experiments according to a method as previously described. [40] Briefly, mice were fasted for 12 h before intraperitoneal injection with 20% glucose solution w/w in proportion to the bodyweight (1 g kg −1 body weight). The blood glucose level was measured at 0, 30, 60, 90, and 120 min after the injection.…”
Section: Methodsmentioning
confidence: 99%